2012
DOI: 10.1186/1866-1955-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Infant siblings and the investigation of autism risk factors

Abstract: Infant sibling studies have been at the vanguard of autism spectrum disorders (ASD) research over the past decade, providing important new knowledge about the earliest emerging signs of ASD and expanding our understanding of the developmental course of this complex disorder. Studies focused on siblings of children with ASD also have unrealized potential for contributing to ASD etiologic research. Moving targeted time of enrollment back from infancy toward conception creates tremendous opportunities for optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 159 publications
2
102
0
2
Order By: Relevance
“…Whilst some studies claim that signs of autistic movement dysfunction are present in the first 4e6 months of age and provide rich descriptive data (Teitelbaum et al, 1998), they lack strong scientific grounding. A more rigorous alternative lies in the study of infant siblings of an autistic individual ("baby sibs"), who, at increased risk of being diagnosed with ASC themselves, can be closely monitored from birth (Newschaffer et al, 2012). We conducted a second, smaller review of these studies, the terms and results of which can be found in Supplementary Materials.…”
mentioning
confidence: 99%
“…Whilst some studies claim that signs of autistic movement dysfunction are present in the first 4e6 months of age and provide rich descriptive data (Teitelbaum et al, 1998), they lack strong scientific grounding. A more rigorous alternative lies in the study of infant siblings of an autistic individual ("baby sibs"), who, at increased risk of being diagnosed with ASC themselves, can be closely monitored from birth (Newschaffer et al, 2012). We conducted a second, smaller review of these studies, the terms and results of which can be found in Supplementary Materials.…”
mentioning
confidence: 99%
“…Therefore, in our response, we will review some of the evidence for ASD biomarkers and consider future directions in terms of identifying biomarkers for ASD, which, when used in conjunction with the early behavioural signs of the disorder, may serve as promising method for identifying predictive biomarkers for ASD has been large-scale, longitudinal prospective studies that investigate high-risk infant siblings of children already diagnosed with ASD (see Elsabbagh & Johnson, 2010;Zwaigenbaum, 2010;Zwaigenbaum, Bryson, Lord, Rogers, Carter, Carver, et al, 2009). This population is at increased genetic risk of developing ASD, and prospective studies of infant development allow the collection of parentreport, biological, environmental, and behavioural data that may signal risk for later developing ASD (Newschaffer, Croen, Fallin, Herz-Picciotto, Nguyen, Lee, et al, 2012). In particular, several studies have investigated aspects of brain function and structure in infant siblings of children with ASD and mapped these early biological signs of ASD onto later behavioural features of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several large-scale longitudinal pregnancy studies, including the Early Autism Risk Longitudinal Investigation (EARLI; Newschaffer et al, 2012) and our Pregnancy Investigation of Siblings and Mothers of Children with Autism (PRISM), have also emerged. These studies provide additional advantages over studies of high-risk infant siblings, as they enable the examination of the pre-, peri-, and post-natal development of infant siblings of children already diagnosed with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…In utero exposures (including medications such as valproic acid, thalidomide, misoprostol, terbutaline or antidepressants), environmental neurotoxicants (e.g., pesticides) and infections (e.g., congenital rubella) have been hypothesized to increase the risk of ASD. 13 Even if confirmed through replication, these exposures would collectively explain only a small number of cases. Early hypotheses that suggested increased risk associated with vaccine exposure (i.e., through the measles-mumpsrubella vaccine or the preservative thimerosal) have been thoroughly disproved.…”
mentioning
confidence: 99%